A process for synthesizing precursor of vanadium phosphate oxide and activated catalysts derive thereof - Yap, Taufiq Yun Hin; Rownaghi, Ali Asghar (2007)

(untitled)
A process for producing VOHPO4.0.5H2O comprises the step of reacting V2O5 and H3PO4 in an alcohol solution under high pressure at the temperature of 100-150C to form the VOHPO4 0.5H2O solid in the alcohol solution. The present invention also relates to a process to obtain a structural and reducibility properties of vanadyl pyrophosphate catalysts for partial oxidation of n-butane of maleic anhydride.